Factor VIII: Perspectives on Immunogenicity and Tolerogenic Strategies - Scott, David W.; Pratt, Kathleen P. (Frontiers in Immunology, 2020)
Therapeutic treatment of bleeds with FVIII can lead to an antibody response that effectively inhibits its function. Herein, we review the factors that contribute to this immunogenicity and possible ways to overcome it.